Deriving intelligence from large data using Hadoop and applying analytics - Tyagi, Vineet (O'Reilly Media, 2011)
"Organizations today possess massive data - in tera- and petabytes - that needs to be effectively collected, stored and processed. Hadoop is a cost effective option that helps manage this big data. To derive real returns from these big data systems, one needs to extract useful insights and business intelligence."--Resource description page.